Nilai-Nilai Pendidikan Islam dalam Tradisi Ngejot: Konsep Edukasi dalam Membangun Keharmonisan dan Kerukunan Antarumat Beragama Berbasis Kearifan Lokal - Baharun, Hasan; Ulum, Mohammad Bahrul; Azhari, Ainun Najib (LP2M IAIN Samarinda, 2018)
This paper presents a ngejot tradition which is a da’wah bil hal that has contributed a lot to the establishment of religious harmony in Bali, especially in Buleleng Regency. This is based on the lack of people that not interested by da’wah bil hal method in Islamic da'wah activities today. This research focuses on the values of Islamic teachings that contained in ngejot tradition, so it is expected to be a solution of harmony among religious communities in Indonesia, especially in Bali. This research uses qualitative method with case study approach. The results showed that, ngejot tradition is an implementation of da’wah bil hal that contains some values such as silaturrahim, shadaqah, musawa and tasamuh. In addition, ngejot is a tradition that able to provide solutions to religious harmony in Bali